Exploring Resource Effectiveness through Training and Organizational Culture among Junior High School Teachers in Bali - Ni Luh Gede Erni Sulindawati; Anak Agung Gede Agung; Basilius Redan Werang (Pedagogi: Jurnal Ilmu Pendidikan, 2026)
The effectiveness of human resources is very influential on teacher performance. The effectiveness of teacher human resources is influenced by various factors such as principal leadership, recruitment, training, organizational culture, and welfare. The results of preliminary interviews conducted with several principals in Middle Schools in Bali Province obtained information that (1) the workforce or teachers recruited did not match the competencies possessed by the teacher, (2) the training conducted did not have a positive impact on improving teacher competency. Good knowledge, expertise and skills are obtained through learning activities at the educational level and training programs (1). The purpose of this study is to analyze the influence of (1) training on the effectiveness of human resources, (2) organizational culture on the effectiveness of human resources, and (3) training, organizational culture on the effectiveness of human resources in Public Junior High School Teachers in Bali Province. Training and organizational culture influence the effectiveness of human resources. Suggestion In order for human resources to be effective, it is necessary to carry out training that is appropriate to the needs of teachers and optimize organizational culture.